Ischemic cerebrovascular event amidst coagulopathy in snake venom envenomation: A case report - Sriman Narayan Reddy; Kamalesh Tagadur Nataraju; Suman Gowdru Rajkumar; Sai Shashank Moota (Asian Journal of Medical Sciences, 2023)
This case report highlights the necessity to have in consideration about the ischemic complications post snake envenomation along with the traditional hemmorhagic events. We report a case of 28-year-old male who developed ischemic cerebral vascular accident post snake envenomation. The manifestations of snakebite may cause severe and sometimes fatal thrombotic or hemorrhagic sequelae. Some of these venom constituents and the mechanisms by which cerebral infarction have been discussed here. Physicians should also take into consideration that snake bite may cause both procoagulant and anticoagulant state. Complications can be prevented by prior identification of the snake bite and early administration of anti-snake venom.